Trabalho e identidade profissional docente em movimentos de desenvolvimento e (des)valorização - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The following research presents the theme "work and professional teaching identity in movements of development and (de)valuation". To this end, it problematizes how teachers from two state schools in a municipality on the western border of the state of Rio Grande do Sul understand and describe their work and their professional identity in contexts of valorization and/or devaluation.As a methodological path, the approach is qualitative and inscribed in the field of human sciences, specifically in the educational area, using professional life cycle studies by Huberman (2000) and the technique of data production and interpretation of oral history narratives autobiographical. Furthermore, two teachers with extensive experience were interviewed, from different areas of knowledge who work in state schools in Itaqui in the interior of RS. Considering issues such as: teacher training, support for professionals involved in the process, accessibility, curricular adequacy, adequate school environment, pedagogical resources, family participation, how each one experienced these phases. As an interpretative movement of the data produced in the dialectical relationship between individual (autobiographical narratives) and collective (teaching), some meanings can be appreciated: a) the interlocutors conveyed security, confidence and a sparkle in their eyes when reporting their positive and negative experiences lived in profession; b) positive experiences lead us to believe we are on the right path; c) and negative ones, encourage the search for personal and professional improvements. In summary, it is understood that the teaching professional path can be built with "serene and bitter" moments and can be modified along this journey. As social and professional recognition of teachers, I hope that this relationship is treated with priority on/by government agendas, because when there is professional appreciation, the positive results of teaching practice in the classroom come by itself, as a process of production of teaching.
Work and professional teaching identity in movements of development and (de)valuation
Keywords: Trabalho docente; Desenvolvimento profissional; (Des) Valorização; Teaching work; Professional development; Devaluation; CNPQ::CIENCIAS EXATAS E DA TERRA